Cysteine oxidation and redox signaling in dopaminergic neurons physiology and in Parkinson's disease (2019)
Parkinson's disease (PD)is a neurological disorder affecting dopaminergic neurons in the nigrostriatal pathways of the brain. PD is a multifactorial disease and its causes should be sought in detrimental interactions between genes and environment. Since early mechanistic studies, excessive oxidation – or oxidative stress – emerged as a recurring and fundamental pathogenic mechanism, and consequently received significant attention. More recent evidence obtained at single-cell resolution, however, indicates that dopaminergic neurons in the substantia nigra display increased oxidation levels also in normal, physiological conditions; differently than pathological oxidation, the importance of this phenomenon is underappreciated. The nigrostriatal dopaminergic system is involved in behavioral strategies that have been under strong evolutionary pressure. It is therefore improbable that physiological oxidation in dopamine neurons is accidental. Here, we review recent literature to argue that moderate oxidation improves redox signaling – which in dopamine neurons is intertwined with electrophysiological activity and is important to regulate dopamine release – and also has a protective role. We also reason that physiological oxidation provides an example of antagonistic pleiotropy therefore offering an advantage during reproductive stages of life while becoming detrimental during aging. Collectively, we believe that these observations provide a new perspective in the biology of dopaminergic neurons and in PD. © 2019 The Authors